APLIKASI MOBILE PEMESANAN TIKET TRAVEL DAN PELACAKAN LOKASI PENUMPANG MENGGUNAKAN GLOBAL POSITIONING SYSTEM (GPS) STUDI KASUS PO. PERSADA LIMPUNG BATANG - Aziz Nurwahidin; Uning Lestari; Suwanto Raharjo (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Travel ticket booking process is still done traditionally which come to the counter or branch office of a travel. Apart from that the most common problem is the drivers difficult to find the location where pick-up passengers. Therefore, this study aims to facilitate the travel of passengers in making reservations or booking tickets for Travel in Yogyakarta. Apart from that provide location information to the travel fleet drivers to pick up passengers at certain locations by using Google Map and Global Positioning System (GPS). Applications built based on Android and the web client server model. The mobile application is used for the passengers and driver. While the web application used by administrators. Mobile application consists of ticket information, customer registration, reservation, payment, and navigation to direct the driver to the passenger pick-up point. While the web application consists of the payment confirmation, processing and reporting of data. Data communication in mobile applications both storage and retrieval of data using an external database system MySQL with support for PHP Programming Language and JSON protocol.